STRENGTHENING INTERNATIONAL COOPERATION TO COMBAT PHISHING IN TRANSNATIONAL CYBERCRIME - Carolina Mirnawati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Cybercrime is around us as a threat in conducting any transactions using electronics. Cybercrime is a global issue both technically through established systems in technological advancements and has a significant impact on socio-economics. Cybercrime has many classifications, including phishing, scams, hacking, and various other types. Phishing is a criminal act that deceives victims to obtain information such as usernames and passwords. Cybercrime continues to develop capabilities to reach actions that have even greater impacts. The serious influence of cybercrime is global, affecting the economy, society, and culture. In particular, economic factors will have a global impact in cybercrime. How to strengthen international cooperation in eradicating phishing in transnational cybercrime. The Budapest Convention has only served as inspiration for the enactment of the ITE Law, without efforts being made to ratify it. Therefore, Indonesia, which has not ratified the convention, is not a member of the Budapest Convention, which causes Indonesia to face problems due to the absence of international cooperation binding.